Preliminary Study Using Medical Student Stressor Questionnaire in Faculty of Medicine Pelita Harapan University - Marlina, Mona (Fakultas Kedokteran Universitas Pelita Harapan, 2020)
Background: Best teaching program for students is certainly the main focus of the faculty. However, we must consider from the student perspective, cause student in Faculty of Medicine is high risk of being stress. Prolonged stress could harm the student physically and or mentally and will disrupt the competencies achievement. One of the validated tools for identifying a group of stressors is Medical Student Stressor Questionnaire (MSSQ).Methods: A cross-sectional univariate done within 30 medical students batch 2016. Age around 16-18 years old consist of 8 male and 21 female.Result: The highest stressor facing by the student was interpersonal related stressors (IRS) mean 2.547, followed by teaching and learning-related stressors (TLRS) 2.485, academic related stressors (ARS) 2.304, group activities related stressors (GARS) 2.259, drive and desire related stressors (DRS) 2.195, and social related stressors (SRS) 2.173.Conclusion: All the stressors domains were in a high level of stress. Further research needed in larger population and level of the study.